Extreme Civil War : Guerrilla Warfare, Environment, and Race on the Trans-Mississippi Frontier - Stith, Matthew M. (Book collections on Project MUSE., 2016)
During the American Civil War the western Trans-Mississippi frontier was host to harsh environmental conditions, irregular warfare, and intense racial tensions that created extraordinarily difficult conditions for both combatants and civilians. Matthew M. Stith's Extreme Civil War focuses on Kansas, Missouri, Arkansas, and Indian Territory to examine the physical and cultural frontiers that challenged Confederate and Union forces alike. A disturbing narrative emerges where conflict indiscriminately beset troops and families in a region that continually verged on social and political anarchy. With hundreds of small fights disbursed over the expansive borderland, fought by civilians -- even some women and children -- as much as by soldiers and guerrillas, this theater of war was especially savage. Despite connections to the political issues and military campaigns that drove the larger war, the irregular conflict in this border region represented a truly disparate war within a war. The blend of violence, racial unrest, and frontier culture presented distinct challenges to combatants, far from the aid of governmental services. Stith shows how white Confederate and Union civilians faced forces of warfare and the bleak environmental realities east of the Great Plains while barely coexisting with a number of other ethnicities and races, including Native Americans and African Americans. In addition to the brutal fighting and lack of basic infrastructure, the inherent mistrust among these communities intensified the suffering of all citizens on America's frontier. Extreme Civil War reveals the complex racial, environmental, and military dimensions that fueled the brutal guerrilla warfare and made the Trans-Mississippi frontier one of the most difficult and diverse pockets of violence during the Civil War.